Pengaruh Lingkar Paha terhadap Kejadian Cedera Tungkai Atas pada Pemain Futsal - Jufenthia Ardelia Wairata; Handy Winata; Hartanto Hartanto (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
Futsal is a highly intense sport that demands good physical ability, in addition to techniques and tactics in players. Exercise makes individuals healthy but may cause injuries. The risk of injury is higher in sports with frequent physical contact with its opponents while competing, like in football or futsal sports. This literature study aimed to evaluate factors that influence thigh injury in futsal. Thighs are the upper part of the limbs that are always related to the incidence of injury, as they vary in size, such as the circumference, length and muscles. Thighs also consist of fatty tissues. Body fat percentage is associated with muscular endurance. Excess fat can limit the flexibility of muscles, thus affect the quality of the movement. Body Mass Index (BMI) which is ideal to minimize the occurrence of overuse musculoskeletal injury and connective tissue disorder is 21-23kg/m2 for any condition. Studies reported that the uninjured group always tends to be more flexible than the injured group. Previous study also reported that the lack of flexibility or muscle rigidity is found to be the risk factor of injury. In addition, the risk of muscle injury increases significantly (up to four times higher) in players who do not heal properly from muscle strength problems. BMI is also one of the factors related to the increased risk of injury to the lower extremities, especially in thigh injuries. Many studies indicate that thigh circumference influence the upper limbs injury in futsal players.